2019
DOI: 10.1016/j.apor.2018.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Sea state estimation using multiple ships simultaneously as sailing wave buoys

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…(2) the low initial investment required 1 and (3) the advantage that ships and offshore platforms can work together to provide worldwide information about the sea conditions, even from remote areas, at anytime. Several works (e.g., [4][5][6]) have shown the accuracy of the estimations of the sea conditions obtained through the VMBs. However, in some sporadic cases, the authors also observed large discrepancies between the inferred directional sea spectra and the measurements adopted as the paradigm for assessing the performance of the VMB.…”
Section: Motivationmentioning
confidence: 96%
“…(2) the low initial investment required 1 and (3) the advantage that ships and offshore platforms can work together to provide worldwide information about the sea conditions, even from remote areas, at anytime. Several works (e.g., [4][5][6]) have shown the accuracy of the estimations of the sea conditions obtained through the VMBs. However, in some sporadic cases, the authors also observed large discrepancies between the inferred directional sea spectra and the measurements adopted as the paradigm for assessing the performance of the VMB.…”
Section: Motivationmentioning
confidence: 96%
“…A global network of directional spectral wave drifters, supplemented as feasible by targeted campaigns such as deploying wave drifters in advance of large storms including hurricanes, should be implemented over the next decade. This network may include new platforms, including ships of opportunity (Nielsen et al, 2019), once their errors are known. Adding many doubtful data should not be thought as a replacement for high quality measurements that are particularly needed for long term climate monitoring and statistics on extreme events.…”
Section: In Situ Observational Systemsmentioning
confidence: 99%
“…Moored buoys are reliable and are the primary means of collecting wave data. This issue of such devices exists because of the performance and maintenance complexity, low-resolution properties, as well as their price and high sensitivity to system errors and weather damage [1][2][3]11,24]. Due to the disadvantages of conventional devices, DWS estimation methods have been extended to process measurements of ship motions (especially the roll, pitch, and heave motions) and their couplings.…”
Section: Estimation Of Dwsmentioning
confidence: 99%
“…Therefore, the connection between encounter and true-wave frequencies is described as a triple-valued function. In other words, the problem exists in the transformation of encountered frequencies into the true-wave frequencies because of the Doppler effect (also known as the triple-valued function problem or the speed-of-advance problem) [3]. The deep-water relationship between the encounter and true wave frequency is given by:…”
Section: Estimation Of Dwsmentioning
confidence: 99%
See 1 more Smart Citation